Video Motion Analysis as a Quantitative Evaluation Tool for Essential Tremor during Magnetic Resonance-Guided Focused Ultrasound Thalamotomy - Mayumi Kaburagi; Futaba Maki; Sakae Hino; Masayuki Nakano; Toshio Yamaguchi; Masahito Takasaki; Hirokazu Iwamuro; Ken Iijima; Jinichi Sasanuma; Kazuo Watanabe; Yasuhiro Hasegawa; Yoshihisa Yamano (MDPI AG, 2023)
The Clinical Rating Scale for Tremor (CRST) is commonly used to evaluate essential tremor (ET) during focused ultrasound (FUS) thalamotomy. However, it faces challenges such as the ceiling effect and test-retest variability. This study explored the utility of videographic motion analysis as an evaluation index for ET. Forty-three patients with ET performed postural tremor and line-drawing tasks recorded on video, and the data were analyzed using motion analysis software. The test-retest and inter-rater reliability, correlations with the CRST and tremor scores, and pre/post-FUS treatment comparisons were analyzed. The video motion analysis showed excellent test-retest and inter-rater reliability. In the postural tremor tasks, video parameter amplitude significantly correlated with the CRST and tremor scores. Similarly, for the line-drawing task, video parameter amplitude showed significant correlations with CRST and tremor scores, effectively addressing the ceiling effect. Regarding post-FUS treatment improvements, changes in the CRST and tremor scores were significantly associated with changes in video parameter amplitude. In conclusion, quantitative analysis of the video motion of ET enables precise evaluation of kinematic characteristics and effectively resolves the ceiling effect and test-retest variability. The video motion analysis score accurately reflected the tremor severity and treatment effects, demonstrating its high clinical utility.